Method for measuring component content of fluorine-chlorine electrolyte for aluminum electrolytic refining

By preparing standard samples and using an XRF spectrometer calibration curve, combined with the tableting method, the problem of the inability to quickly and accurately determine the content of the fluorochloro-electrolyte for aluminum electrolytic refining in the prior art is solved, and a fast and accurate detection effect is achieved.

CN119555718APending Publication Date: 2025-03-04ZHENGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411744805.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art cannot quickly and accurately determine the component content of the fluorochloro-electrolyte for aluminum electrolytic refining, resulting in complex detection steps and poor aging.

Method used

By preparing a series of standard samples, using an XRF spectrometer to make calibration curves, and using tableting method to make samples, the rapid analysis of the samples to be tested is achieved.

Benefits of technology

It realizes rapid and accurate detection of the content of the fluorochloro-electrolyte for aluminum electrolytic refining, simplifies the operation process, and improves the timeliness and accuracy of the detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119555718A_ABST
    Figure CN119555718A_ABST
Patent Text Reader

Abstract

The invention discloses a method for measuring the component content of fluorine-chlorine electrolyte for aluminum electrolytic refining, which comprises the following steps of: preparing a series of standard samples including the content range of fluorine-chlorine electrolyte elements in aluminum electrolytic refining by adopting a high-purity reagent, preparing a sample by adopting a tabletting method, measuring and drawing a calibration curve by XRF (X-Ray Fluorescence), and determining the component content of fluorine-chlorine electrolyte for aluminum electrolytic refining. And preparing a detection sample by adopting the same sample preparation mode, quantitatively measuring the contents of fluorine, aluminum, sodium, barium and chlorine elements in the to-be-detected sample by utilizing XRF (X-Ray Fluorescence), and calculating the component content of the fluorine-chlorine electrolyte. The method has the advantages that the content of each element of the fluorine-chlorine electrolyte in the aluminum electrolytic refining can be rapidly measured before the cell, the sample preparation is simple, the operation is convenient, the accuracy is high, the precision is high and the like, and the fluorine-chlorine electrolyte components in the aluminum electrolytic refining can be detected in real time, so that accurate regulation and control are realized, and the smooth electrolysis is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for determining the content of fluorine and chlorine electrolyte components for aluminum electrolytic refining, and belongs to the field of aluminum electrolytic refining. Background Art

[0002] Three-layer liquid aluminum electrolytic refining is an important production method for producing 99.99% refined aluminum. The electrolytic cell is composed of three layers of liquid. The lower layer of liquid is generally composed of Cu-Al anode alloy, and its density is generally 3.4-3.7g / cm 3 The middle layer is composed of molten salt electrolyte, and its density is generally 2.7-2.8g / cm 3 The upper liquid is made of refined pure aluminum with a density of 2.3g / cm 3 . The three-layer liquid aluminum electrolytic refining electrolyte usually adopts a fluorine-chlorine system composed of cryolite, aluminum fluoride, barium chloride and sodium chloride. The fluorine-chlorine system has the advantages of low initial crystallization temperature, good conductivity, moderate density and low electrolysis voltage. However, in industrial production, the hydrolysis problem of fluorine-chloride electrolyte is more serious, which causes the composition of the electrolyte to change and affects the normal electrolysis. It is necessary to analyze and monitor the electrolyte composition in real time before the tank, and correct the composition when necessary to ensure the stable electrolytic refining.

[0003] There are many single-component detection methods in fluorine-chlorine electrolytes used for aluminum electrolytic refining. For example, the analysis and detection methods for fluorine in aluminum fluoride and sodium fluoride include distillation-thorium nitrate titration volumetric method, fluoride ion selective electrode method and ion chromatography; the barium in barium chloride is analyzed by ICP analysis; the chlorine in barium chloride and sodium chloride is analyzed by ion chromatography; the sodium in sodium fluoride and sodium chloride can be analyzed by atomic absorption spectroscopy; the aluminum in aluminum fluoride and cryolite is analyzed by EDTA volumetric method.

[0004] The above method can only be used for elemental analysis in pure substances or typical substances. However, for fluorine-chlorine electrolytes, it is difficult to accurately determine because a small amount of solid particles still exist after the electrolyte is digested. Even if a pretreatment method that can completely digest is developed, multiple types of instruments and methods are still required to coordinate the determination of each element in the electrolyte. It is impossible to use a single method for determination, which will inevitably lead to complex detection steps and poor timeliness. So far, there is still no method for rapid determination of fluorine-chlorine electrolytes used in aluminum electrolytic refining.

[0005] "Application of X-ray Fluorescence (XRF) Analysis Technology in Aluminum Industry Analysis" discusses in detail the application of XRF technology in the aluminum industry. It is mainly used to analyze the molecular ratio of cryolite and the element content in aluminum fluoride (Zhang Aifen, "Determination of the composition of cryolite by X-ray fluorescence spectrometry", Ma Huixia, "Determination of the major and minor components of aluminum fluoride by XRF melting method"), and formulates corresponding standards (XRF analysis of element content in cryolite and aluminum fluoride (YS / T273.14-2008, YS / T581.16-2008, YS / T581.18-2012).

[0006] However, the electrolyte components of fluorinated chloride electrolyte used for aluminum electrolytic refining are very different from those of primary aluminum electrolysis, and the XRF method cannot be simply applied. Specifically, first, fluorinated chloride electrolytes contain barium and chlorine, and the barium and chlorine contents (wt.%) account for a large proportion, accounting for about 40% and 23% respectively, which will change the absorption and enhancement effect between elements, resulting in different calibration curves of samples. Secondly, there are the same elements between the components of fluorinated chloride electrolytes, such as barium chloride and sodium chloride both contain chlorine, and sodium fluoride and sodium fluoride both contain sodium, which will produce a mineral effect (both phases contain the elements to be analyzed, but the absorption of their analysis lines is different), resulting in different calibration curves of samples. These factors will affect the accuracy of quantitative analysis. Therefore, it is necessary to prepare standard samples of the fluorine-chlorine system to correct these matrix effects and establish an XRF analysis method for measuring fluorinated chloride electrolytes.

[0007] The purpose of the present invention is to establish a method for determining the content of fluorine and chlorine electrolyte components used in aluminum electrolytic refining, in order to solve the problem that the content of fluorine and chlorine electrolyte components cannot be determined quickly at one time. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for determining the content of fluorine and chlorine electrolyte components for aluminum electrolytic refining, which can solve the problem of being unable to quickly determine the content of fluorine and chlorine electrolyte components in one time, and at the same time has the advantages of accurate and rapid detection results.

[0009] In order to achieve the above object, the technical solution of the present invention is to provide a method for determining the content of fluorine and chlorine electrolyte components for aluminum electrolytic refining, comprising the following steps:

[0010] (1) heating and drying high-purity barium chloride dihydrate;

[0011] (2) Mixing the dried barium chloride with high-purity sodium chloride, aluminum fluoride, and sodium fluoride to prepare a series of standard samples covering the range of fluorine and chlorine electrolyte elements for aluminum electrolytic refining;

[0012] (3) The standard sample is heated to a molten state, kept warm for a period of time, and then cooled, and then the element value of the standard sample is determined;

[0013] (4) The standard samples were first ground into powder, and then prepared by tableting. The calibration curves of fluorine, aluminum, sodium, barium, and chlorine were then prepared using an XRF spectrometer.

[0014] (5) The fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested is ground and pressed into a tablet in the same manner as the standard sample, and the sample to be tested is analyzed using an XRF spectrometer to determine the content of each element therein, and the content of each component in the sample to be tested is calculated.

[0015] Furthermore, in step (1), the heating temperature of barium chloride dihydrate is 200-500° C. and the heating time is 2-5 hours.

[0016] Furthermore, the purity of the aluminum fluoride, sodium fluoride, barium chloride and sodium chloride used to prepare the standard sample in step (2) is ≥99.9%; the content (wt.%) of each element in the standard sample prepared in step (2) is in the range of 10%-40% for fluorine, 2%-20% for aluminum, 2%-20% for sodium, 30%-50% for barium and 10%-30% for chlorine.

[0017] Furthermore, in step (2), the number of standard samples with different element content ranges is ≥5.

[0018] Furthermore, the heating temperature in step (3) is 700-1000° C., and the insulation time is 5-30 min.

[0019] Preferably, the heating temperature in step (3) is 800-900° C., and the insulation time is 10-15 min.

[0020] Furthermore, in the step (4), the particle size of the sample after grinding is ≥200 mesh; when tableting, 1-5g of the powdered standard sample is taken and the sample is prepared by the boric acid edging-substrate tableting method, wherein the boric acid is analytically pure, the tableting pressure is 5-40t, and the holding time is 5-40s.

[0021] Preferably, during tableting in step (4), 1.5-3 g of powdered standard sample is taken and sample is prepared by boric acid edging-substrate tableting method, wherein the boric acid is analytical grade, the tableting pressure is 20-40t, and the holding time is 20-40s.

[0022] Further, the R of the calibration curve of each element in the fluorine-chlorine electrolyte in step (4) 2 ≥0.99.

[0023] Furthermore, in the step (4), the measured content (wt.%) of the elements in the sample to be tested is in the range of 10%-40% for fluorine, 2%-20% for aluminum, 2%-20% for sodium, 30%-50% for barium, and 10%-30% for chlorine.

[0024] Furthermore, in step (4), when the content of any element in the standard sample differs from the content of any element measured by the X-ray fluorescence spectrometer by ≥0.5wt.%, recalibration or formulation of a calibration curve is required.

[0025] Furthermore, in step (5), the sample to be tested is processed strictly in accordance with the grinding and tableting method of the standard sample.

[0026] The content (wt.%) range of each element in the standard sample prepared in step (2) should be the same as the content range of each element in the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested, or cover the content range of each element in the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested.

[0027] Beneficial Effects

[0028] (1) Standard samples. At present, the country and the aluminum industry do not have standard samples of fluorine and chlorine electrolytes in aluminum electrolytic refining, so an XRF standard sample method and standard sample based on the present application system are created. The present invention reduces the absorption enhancement effect and mineral effect between elements by heating and melting the standard sample, and the regression coefficient of the obtained standard curve is good (R 2 >0.99), which provides a basis for the rapid detection of fluorine and chlorine electrolyte components used in aluminum electrolytic refining by XRF.

[0029] (2) Pre-tank detection. The chemical analysis method requires the sample to be tested to be digested, and the digestion process takes more than three hours, or even longer. At the same time, there is an incomplete digestion phenomenon, which affects the accuracy of the result. The method of the present invention only needs to crush and grind the sample to be tested, and it only takes a few minutes to meet the particle size requirements, and the XRF spectrometer takes about 10 minutes to analyze the sample. Therefore, compared with other more complex chemical analysis methods, the detection time can be greatly shortened. It only takes more than ten minutes to obtain the detection results of the fluorine and chlorine electrolyte component content, realizing rapid analysis of the electrolyte component content before adding materials, and accurately controlling the amount of material added.

[0030] (3) Simple operation. Standard samples only need to be treated with moisture-proof treatment, and the samples to be tested do not need complicated pre-treatment such as digestion process. Simplifying the sample processing steps, reducing the difficulty of operation, and reducing the workload of the testers.

[0031] (4) Accurate data. Fluorine-chlorine electrolytes used in aluminum electrolytic refining contain a large amount of fluorine and chlorine elements. If the melting method is used, the fluorine and chlorine elements will inevitably volatilize during high-temperature melting, which directly affects the determination of fluorine and chlorine elements. This method uses the tableting method to prepare samples, avoiding the volatilization of fluorine and chlorine elements. By reducing the powder particle size and reducing the particle size effect, a highly accurate test result is obtained.

[0032] (5) Good data reproducibility. This method can obtain high-precision test results. The same sample is measured multiple times, and the difference between the results is small, with RSD% <0.26%. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is the calibration curve of each element in Example 1.

[0034] Figure 2 This is a comparison of the X-ray fluorescence intensity of the standard sample prepared by direct grinding in Comparative Example 1 and the sample to be tested.

[0035] Figure 3 The figure is a comparison of the X-ray fluorescence intensity of the standard sample of the present invention and the sample to be tested in comparative example 1.

[0036] Figure 4 The X-ray fluorescence intensity of each element in Comparative Example 2 changes with grinding time. DETAILED DESCRIPTION

[0037] The specific implementation modes of the present invention are further described in detail below in conjunction with the embodiments.

[0038] Example 1: A method for determining the content of fluorine and chlorine electrolyte components for aluminum electrolytic refining

[0039] (1) drying high-purity barium chloride dihydrate at 200° C. for 4 h to completely remove crystal water;

[0040] (2) Mix dried barium chloride with sodium chloride, aluminum fluoride, and sodium fluoride high-purity reagents to prepare a series of 7 standard samples covering the range of fluorine and chlorine electrolyte elements for aluminum electrolytic refining, wherein the purity of aluminum fluoride, sodium fluoride, barium chloride, and sodium chloride is 99.99%. The content (wt.%) of each element in the standard samples is 15.15-31.21% for fluorine, 3.54%-11.57% for aluminum, 5.71%-11.28% for sodium, 32.27%-44.13% for barium, and 17.94%-24.61% for chlorine;

[0041] (3) Heat the standard sample to 800°C, keep it at this temperature for 10 min, then cool it down and determine the element value of the standard sample;

[0042] (4) The standard sample was ground and sieved in a glove box to make the particle size of the powder sample reach 200 mesh;

[0043] (5) Weigh 2 g of powder sample and press it into tablets using boric acid edging-backing, with a tablet press pressure of 35 t and a holding time of 30 s;

[0044] (6) The prepared standard samples were used to make calibration curves for aluminum, barium, sodium, chlorine, and fluorine on an X-ray fluorescence spectrometer. 2 They are 0.9988, 0.9987, 0.9964, 0.9961, and 0.9929 respectively. The calibration curves of each element are shown in Figure 1 As shown;

[0045] (7) Take out the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested, grind and press the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested into a sheet in the same manner as the preparation of the standard sample in the same manner as the steps (4) and (5), ensure that the sample preparation conditions are the same as those of the standard sample, and then use an X-ray fluorescence spectrometer to measure the content of each element, and calculate the content of each component in the electrolyte.

[0046] The content of each component was calculated from the element content (Table 1).

[0047] Table 1 XRF analysis results of components

[0048]

[0049] It can be seen from Table 1 that the relative errors of the measured values ​​of the fluorine-chlorine electrolyte components for aluminum electrolytic refining and the standard values ​​are both less than 10%, and the accuracy is relatively high.

[0050] The same sample was tested multiple times, and the precision analysis results are shown in Table 2. The standard deviation (SD) of the content of each element in the fluorine-chlorine electrolyte is ≤0.05, and the relative standard deviation (RSD) is ≤0.26%, with high precision.

[0051] Table 2 Element precision test results

[0052]

[0053]

[0054] Example 2: A method for determining the content of fluorine and chlorine electrolyte components for aluminum electrolytic refining

[0055] (1) drying high-purity barium chloride dihydrate at 300° C. for 5 h to completely remove crystal water;

[0056] (2) Mix dried barium chloride with sodium chloride, aluminum fluoride, and sodium fluoride high-purity reagents to prepare a series of 5 standard samples covering the range of fluorine and chlorine electrolyte elements for aluminum electrolytic refining, wherein the purity of aluminum fluoride, sodium fluoride, barium chloride, and sodium chloride is 99.99%. The content (wt.%) of each element in the standard samples is 10.00%-30.31% for fluorine, 3.54%-20.00% for aluminum, 2.00%-11.43% for sodium, 30.00%-44.13% for barium, and 18.55%-30.00% for chlorine;

[0057] (3) Heat the standard sample to 850°C, keep it at this temperature for 15 min, then cool it down and determine the element value of the standard sample;

[0058] (4) The standard sample was ground and sieved in a glove box to make the particle size of the powder sample reach 300 mesh;

[0059] (5) Weigh 1.5 g of powder sample and press it into tablets using boric acid edging-backing, with a tablet press pressure of 20 t and a holding time of 40 s;

[0060] (6) The prepared standard samples were used to prepare calibration curves for fluorine, aluminum, sodium, barium, and chlorine elements on an X-ray fluorescence spectrometer. 2 They are 0.9911, 0.9989, 0.9937, 0.9987, 0.9991 respectively;

[0061] (7) Take out the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested, grind and press the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested into a sheet in the same manner as the preparation of the standard sample in the same manner as the steps (4) and (5), ensure that the sample preparation conditions are the same as those of the standard sample, and then use an X-ray fluorescence spectrometer to measure the content of each element, and calculate the content of each component in the electrolyte.

[0062] The content of each component was calculated based on the element content (Table 3).

[0063] Table 3 XRF analysis composition determination results

[0064]

[0065] It can be seen from Table 3 that the relative errors of the measured values ​​of the fluorine-chlorine electrolyte components for aluminum electrolytic refining and the standard values ​​are both less than 5%, and the accuracy is relatively high.

[0066] The same sample was tested several times, and the results of precision analysis are shown in Table 4. The SD of the content of each component in the fluorine-chlorine electrolyte was ≤ 0.02, and the RSD was ≤ 0.14%, with high precision.

[0067] Table 4 Element precision test results

[0068]

[0069] Example 3: A method for determining the content of fluorine and chlorine electrolyte components for aluminum electrolytic refining

[0070] (1) drying high-purity barium chloride dihydrate at 500° C. for 2 h to completely remove crystal water;

[0071] (2) Mix dried barium chloride with sodium chloride, aluminum fluoride, and sodium fluoride high-purity reagents to prepare a series of 6 standard samples covering the range of fluorine and chlorine electrolyte elements for aluminum electrolytic refining, wherein the purity of aluminum fluoride, sodium fluoride, barium chloride, and sodium chloride is 99.99%. The content (wt.%) of each element in the standard samples is 17.51%-40.00% for fluorine, 2.00%-11.80% for aluminum, 6.67%-20.00% for sodium, 32.93%-50.00% for barium, and 10.00%-24.27% for chlorine;

[0072] (3) Heat the standard sample to 900°C, keep it at this temperature for 10 min, then cool it down and determine the element value of the standard sample;

[0073] (4) The standard sample was ground and sieved in a glove box to make the particle size of the powder sample reach 200 mesh;

[0074] (5) Weigh 3 g of powder sample and press it into tablets using boric acid edging-backing, with a tablet press pressure of 40 t and a holding time of 20 s;

[0075] (6) The prepared standard samples were used to make calibration curves for fluorine, aluminum, sodium, barium, and chlorine elements on an X-ray fluorescence spectrometer. 2 They are 0.9954, 0.9963, 0.9943, 0.9986, 0.9983 respectively;

[0076] (7) Take out the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested, grind and press the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested into a sheet in the same manner as the preparation of the standard sample in the same manner as the steps (4) and (5), ensure that the sample preparation conditions are the same as those of the standard sample, and then use an X-ray fluorescence spectrometer to measure the content of each element, and calculate the content of each component in the electrolyte.

[0077] The content of each component was calculated by element content (Table 5).

[0078] Table 5 XRF analysis results of components

[0079]

[0080] It can be seen from Table 5 that the relative errors of the measured values ​​of the fluorine-chlorine electrolyte components for aluminum electrolytic refining and the standard values ​​are both less than 4%, and the accuracy is relatively high.

[0081] The same sample was tested several times, and the results of precision analysis are shown in Table 6. The SD of the content of each component in the fluorine-chlorine electrolyte was ≤ 0.02, and the RSD was ≤ 0.10%, with high precision.

[0082] Table 6 Element precision test results

[0083]

[0084] Comparative Example 1

[0085] (1) drying high-purity barium chloride dihydrate at 200° C. for 4 h to completely remove crystal water;

[0086] (2) Mixing dried barium chloride with sodium chloride, aluminum fluoride, and sodium fluoride high-purity reagents to prepare a series of standard samples covering the range of fluorine and chlorine electrolyte elements for aluminum electrolytic refining, wherein the purity of aluminum fluoride, sodium fluoride, barium chloride, and sodium chloride is 99.99%. The content (wt.%) of each element in the standard samples is 15.15-31.21% for fluorine, 3.54%-11.57% for aluminum, 5.71%-11.28% for sodium, 32.27%-44.13% for barium, and 17.94%-24.61% for chlorine;

[0087] (3) Grind and sieve the standard sample in a glove box to make the particle size of the powder sample reach 200 mesh;

[0088] (4) Weigh 2 g of powder sample and press it into tablets using boric acid edging-backing, with a tablet press pressure of 35 t and a holding time of 30 s;

[0089] (5) Using the prepared standard samples on an X-ray fluorescence spectrometer to create calibration curves for aluminum, barium, sodium, chlorine, and fluorine;

[0090] (6) Take out the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested, grind and press the fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested into a sheet in the same manner as the steps (4) and (5) for preparing the standard sample, ensure that the sample preparation conditions are the same as those of the standard sample, and then use an X-ray fluorescence spectrometer to measure the content of each element, and calculate the content of each component in the electrolyte.

[0091] When the element content of the standard sample is the same as that of the sample to be tested, the X-ray fluorescence intensity result is as follows: Figure 2As shown, the detection requirements of the sample to be tested cannot be met. This is because the standard sample is made of high-purity reagent powders of barium chloride, sodium fluoride, sodium chloride and aluminum fluoride mixed, ground and pressed into tablets. The physical phase of the standard sample is composed of BaCl2, NaCl, NaF and AlF3, while the fluorine-chlorine electrolyte to be tested is composed of NaCl, BaClF, BaCl2 and Na3 (AlF6). Therefore, there is a large mineral effect. At the same time, the absorption enhancement effect between various elements (barium and chlorine elements) leads to large differences in the X-ray fluorescence intensity of each element, making it impossible to obtain accurate element content. The present invention adopts the method of heating barium chloride, sodium fluoride, sodium chloride and aluminum fluoride at high temperature and then cooling them to generate NaCl, BaClF, BaCl2 and Na3 (AlF6) substances, thereby reducing the influence of mineral effects and the absorption enhancement effect of barium and chlorine. When the content of each element in the standard sample of the present invention is the same as the content of the element in the sample to be tested, the X-ray fluorescence intensity of aluminum, sodium, barium, chlorine and fluorine is as shown in FIG. Figure 3 As shown, the X-ray fluorescence intensity of each element is basically the same, so the sample can be accurately measured.

[0092] Comparative Example 2

[0093] (1) drying high-purity barium chloride dihydrate at 200° C. for 4 h to completely remove crystal water;

[0094] (2) Mix the dried barium chloride with sodium chloride, aluminum fluoride, and sodium fluoride high-purity reagents to prepare a series of standard samples covering the content range of fluorine and chlorine electrolyte elements for aluminum electrolytic refining, wherein the purity of aluminum fluoride, sodium fluoride, barium chloride, and sodium chloride is 99.99%. The content (wt.%) of each element in the standard samples is 15.15-31.21% for fluorine, 3.54%-11.57% for aluminum, 5.71%-11.28% for sodium, 32.27%-44.13% for barium, and 17.94%-24.61% for chlorine.

[0095] (3) Heat the standard sample to 800°C, keep it at this temperature for 10 min, then cool it down and determine the element value of the standard sample;

[0096] (4) The standard sample was ground to 200 mesh in air;

[0097] (5)(6)(7) Steps are the same as those in Example 1.

[0098] The X-ray fluorescence intensity of each element changes as shown in Figure 4As shown, when grinding in the air, as the grinding time increases, the sample continuously absorbs moisture during the grinding process, causing the X-ray fluorescence intensity of each element in the sample to change, so the exact content of each element cannot be accurately determined, and the composition of the fluorine and chlorine electrolyte cannot be accurately measured. The present invention adopts grinding in a glove box, which can avoid the moisture absorption of the fluorine and chlorine electrolyte during the grinding process, reduce the change of the X-ray fluorescence intensity of the element to be measured, and keep it stable to achieve the conditions for accurate measurement.

[0099] Comparative Example 3

[0100] The chemical digestion for determining the barium, aluminum and sodium elements in the fluorine-chlorine electrolyte is as follows: put the sample in a platinum crucible, add a small amount of water and 4 mL of perchloric acid, heat the platinum crucible on a heating table, heat at low temperature until the white smoke disappears, add 5 mL of hydrochloric acid solution (the volume ratio of hydrochloric acid to water is 1:1) and 30 mL of deionized water after cooling, then put it on a heating table, heat at low temperature until the solution is clear, filter and adjust the volume to a volumetric flask. It takes 4-5 hours to digest the sample in this process, and it may not be completely digested.

[0101] The determination of fluorine in fluorine-chlorine electrolyte is as follows: add the dry sample to a nickel crucible with a small amount of sodium hydroxide at the bottom, then add sodium hydroxide on the sample to cover the sample surface, and heat it in a high-temperature heating furnace. Take it out after a period of time, cool it in the air, then pour in hot water, and leaching it repeatedly. After leaching, transfer the liquid to a polyethylene beaker, add 5mL of hydrochloric acid, cool it to room temperature, filter it, pour it into a colorimetric tube, add one or two drops of bromocresol purple indicator, and add hydrochloric acid drop by drop until the color of the solution changes from blue-purple to yellow, and then use a fluoride ion selective electrode for determination.

[0102] The determination of chlorine in fluorine-chlorine electrolyte is as follows: put the sample into a nickel crucible with sodium carbonate on the bottom, then add sodium carbonate on the sample, put it into a muffle furnace for heating for a period of time, and then take it out to cool; pour 300mL of water into a two-necked round-bottom flask and put in glass beads; put the sample in the nickel crucible into a three-necked round-bottom flask, and add 60mL of sulfuric acid solution (the volume ratio of sulfuric acid to water is 2:1); heat the two-necked round-bottom flask and the three-necked round-bottom flask, control the temperature to control the water vapor flow, and after heating and distilling for a period of time, remove the receiving bottle; finally, filter the solution in the receiving bottle and add it into a plastic volumetric flask, and determine the content of chlorine by ion chromatography.

[0103] These determination methods require a lot of time, reagents and instruments, resulting in poor timeliness and unable to meet the requirements of pre-tank detection. However, the method of the present invention only requires the sample to be ground and sieved in a glove box so that the particle size of the powder sample reaches 200 meshes; 2g of powder sample is weighed, and the tablet is pressed using a boric acid rim-substrate, with a tablet press pressure of 35t and a holding time of 30s. The operation is simple, the time required is short, pre-tank detection can be achieved, and the results are accurate. Table 7 compares the results after XRF and chemical digestion. The results show that the results of this method are close to those of chemical digestion, and the results are reliable.

[0104] Table 7 Comparison of XRF and chemical digestion analysis results

[0105]

[0106] Comparative Example 4

[0107] When the fluorine-chlorine electrolyte to be tested is prepared by the melting plate method, the fluorine-chlorine electrolyte sample to be tested is first added to the flux (the mass percentage of Li2B4O7 and LiBO2 is 67:33), and the mass percentage of Li2B4O7 and LiBO2 is 1:10, and ammonium iodide mold release agent is added, and the glass sheet is made after heating and melting and cooling. The contents of fluorine and chlorine elements in the glass sheet are measured as shown in Table 8.

[0108] Table 8 F and Cl content in glass sheets

[0109]

[0110] Since the fluorine and chlorine elements contained in the fluorine-chlorine electrolyte will volatilize in large quantities during the melting process, it is impossible to accurately measure the fluorine and chlorine elements, that is, it is impossible to calculate the content of each component in the fluorine-chlorine electrolyte. The present invention adopts direct tableting of the sample for measurement, which avoids the volatilization of fluorine and chlorine elements and ensures the accuracy of the measurement results.

Claims

1. A method for determining the content of fluorine and chlorine electrolyte components for aluminum electrolytic refining, characterized in that: The steps include: (1) heating and drying high-purity barium chloride dihydrate; (2) Mixing the dried barium chloride with high-purity sodium chloride, aluminum fluoride, and sodium fluoride to prepare a series of standard samples covering the range of fluorine and chlorine electrolyte elements for aluminum electrolytic refining; (3) The standard sample is heated to a molten state, kept warm for a period of time, and then cooled, and then the element value of the standard sample is determined; (4) The standard samples were first ground into powder, and then prepared by tableting. The calibration curves of fluorine, aluminum, sodium, barium, and chlorine were then prepared using an XRF spectrometer. (5) The fluorine-chlorine electrolyte for aluminum electrolytic refining to be tested is ground and pressed into a tablet in the same manner as the standard sample, and the sample to be tested is analyzed using an XRF spectrometer to determine the content of each element therein, and the content of each component in the sample to be tested is calculated.

2. The method according to claim 1, characterized in that In the step (1), the heating temperature of barium chloride dihydrate is 200-500° C. and the heating time is 2-5 hours.

3. The method according to claim 1, characterized in that The purity of the aluminum fluoride, sodium fluoride, barium chloride and sodium chloride used to prepare the standard sample in step (2) is ≥99.9%; the content (wt.%) of each element in the standard sample prepared in step (2) is in the range of 10%-40% for fluorine, 2%-20% for aluminum, 2%-20% for sodium, 30%-50% for barium and 10%-30% for chlorine.

4. The method according to claim 1, characterized in that: In the step (2), the number of standard samples with different element content ranges is ≥5.

5. The method according to claim 1, characterized in that The heating temperature in step (3) is 700-1000° C., and the insulation time is 5-30 minutes.

6. The method according to claim 1, characterized in that In the step (4), the particle size of the sample after grinding is ≥200 mesh; when tableting, 1-5g of the powdered standard sample is taken and the sample is prepared by the boric acid edging-substrate tableting method, wherein the boric acid is analytically pure, the tableting pressure is 5-40t, and the holding time is 5-40s.

7. The method according to claim 1, characterized in that The R of the calibration curve of each element in the fluorine-chlorine electrolyte in step (4) 2 ≥0.

99.

8. The method according to claim 1, characterized in that The measured content (wt.%) of the elements in the sample to be tested in step (4) is in the range of 10%-40% for fluorine, 2%-20% for aluminum, 2%-20% for sodium, 30%-50% for barium and 10%-30% for chlorine.

9. The method according to claim 1, characterized in that: In the step (4), when the content of any element in the standard sample differs from the content of any element measured by the X-ray fluorescence spectrometer by ≥0.5wt.%, recalibration or formulation of a calibration curve is required.

10. The method according to claim 1, characterized in that In the step (5), the sample to be tested is processed strictly according to the grinding and tableting method of the standard sample.

Citation Information

Patent Citations

  • Method for simultaneously detecting content of every element in aluminum electrolyte

    CN107037038A

  • Method for quantitatively measuring element content of aluminium electrolysis cell waste cathode bottom carbon block

    CN110687148A

  • Method for measuring fluorine content in fluorine-loaded aluminum oxide by X-ray fluorescence spectrometry

    CN113237907A

  • X-ray flourescent quickly analysing method of fine aluminium electrolytic component

    CN1869670A